The development of intergroup bias in childhood: how social norms can shape children's racial behaviours - Monteiro, M. (2015)
The present research examined the developmental course of racial behaviours in childhood. It tested the hypothesis that White children's expressions of racial prejudice do not necessarily decline in middle childhood due to the development of particular cognitive skills but that instead, as argued by the socio-normative approach, children older than seven will go on expressing prejudiced attitudes under appropriate conditions. This would be explained by the presence of an anti-racism norm, along with the existence of values promoting equal rights, which impede blatant expressions of racism. In the first study 283 White children aged 6-7 and 9-10 years performed a task of resource allocation to White and Black target children in conditions of high (White interviewer was present) or low (White interviewer was absent) salience of the anti-racist norm. The 6- to 7-year-old children discriminated against the Black target in both conditions whereas older children discriminated against the Black child only when the anti-racist norm was not salient. In Study 2, 187 White children aged 6- 7 and 9-10 years performed the same resource allocation task in conditions of explicit activation of similarity vs dissimilarity or egalitarian vs merit-based norms regarding race relations. Supporting the hypothesis of the role of racist or anti-racist norms on the expression of intergroup discrimination, results have again shown that 6- to 7year-old children discriminated against the Black target in both conditions while older children presented significantly different prejudiced/nonprejudiced behaviours consistent with the activated norms. These results were discussed in terms of the need for a reanalysis of the assumptions and research results of the cognitive-developmental theory and of further developments in the socio-normative approach regarding the development of prejudice in childhood.